A Look Back: Kappan authors on children and youth. (April 2019) - Preston, Teresa
Teaching children well requires an understanding of them, and so multiple Kappan authors over the years have examined how societal and cultural shifts have affected young people. In this column, Teresa Preston provides a sampling of authors' views on children and youth. Some authors have taken a negative view, bewailing the behavior of young people or fretting over their growing alienation. In many cases, authors have looked to adults as the source of students' problems, whether because of how adults have chosen to structure their lives or because of the policies adults have advocated .